2016
DOI: 10.5901/mjss.2016.v7n2s1p265
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Entrepreneurial Resources to Competitive Advantage: The Role of Social Capital and Marketing capability

Abstract: Since small businesses are economic engines in many nations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
3
1
Order By: Relevance
“…In the findings, social capital was found not to significantly influence competitive advantage. Contrary to the previous findings of Pratono et al (2016), and Al-daibat (2017) which supported the influence.…”
Section: Conceptual Frameworkcontrasting
confidence: 92%
See 1 more Smart Citation
“…In the findings, social capital was found not to significantly influence competitive advantage. Contrary to the previous findings of Pratono et al (2016), and Al-daibat (2017) which supported the influence.…”
Section: Conceptual Frameworkcontrasting
confidence: 92%
“…It also concluded that the effects of social capital are equivocal but mostly negative. But on the contrary, Pratono et al (2016) in a study conducted in Indonesia examining the impact of social capital and moderating impact of marketing on firm performance, found that organizations can seize business opportunities and attain competitive advantage by exploiting social capital constructs such as trust and cognition. Social capital was found to be a valuable resource that enables organizations to gain a competitive advantage (Pratono et al, 2016).…”
Section: Conceptual Frameworkmentioning
confidence: 96%
“…According to Pratono et al(2016), the role of social capital is still underused by SMEs in improving technology and achieving competitive advantage, and improving company performance. For this reason, it is necessary to optimize intangible assets.…”
Section: Social Capital Competitive Advantage and Performancementioning
confidence: 99%
“…On the other hand, [15] found out that more networked traders in Madagascar had higher profit margins compared to the less networked traders. While [16], notes that social capital serves as complementary mediator which supports marketing capability consequently enhancing performances. Though studies on social capital have existed for quite some time, the role it plays in influencing marketing capability and performance has not been explored.…”
Section: Introductionmentioning
confidence: 99%